Anticoagulant initiation after cardioembolic stroke: practical timing and options - Manorenj, Sandhya; Kumar, Sara Sravan; Shashanka, Chillapuram (International Journal Of Community Medicine And Public Health, 2025)
Cardioembolic Stroke (CES) is a leading cause of Acute Ischemic Stroke (AIS) and is linked to worse outcomes. There is a notably increased risk of “hemorrhagic transformation” (HT) in CES cases, where anticoagulant therapy is essential for patients with atrial fibrillation (AF) to prevent future strokes. Additionally, larger infarcts are associated with a higher risk of HT, effectively doubling the mortality risk. Currently, there are no clear guidelines connecting infarct size to “anticoagulation” decisions or management of HT cases. This review specifically focuses on the timing of “anticoagulation” initiation in patients with AF. Out of 380 articles evaluated, 50 relevant studies were included in this review. Generally, existing guidelines recommend starting “anticoagulation” between 4 to 14 days after anAIS. The review seeks to summarize current research on early versus late “anticoagulation” initiation in AF patients who experience AIS, providing clinicians with practical insights on optimal timing and the selection of effective and safe anticoagulants.